ROLE PLAY TO IMPROVE STUDENTS’ PARTICIPATION IN LEARNING ENGLISH: A REPORT FROM A HIGH SCHOOL IN EAST JAVA - Nunung Safira Abdullah Hamid (English Didactic, 2021)
The study aims to examine to what extent a role-play method can increase students’ participation in English learning. Classroom Action Research (CAR) is conducted to achieve the purpose. Research data are collected through observation to look at students’ participation and questionnaires that are distributed throughout 3 cycles of role-play implementation. The study shows that the role-play method can be enacted to improve students’ participation in learning English. There is also an increase in students’ participation during the three cycles of role-play enactment which proves that this method has a prominent potential in enhancing students’ English learning engagement.